Enhancing the efficiency of a dual three-phase permanent magnet synchronous motor with modified switching table for direct torque control - Labchir, Fouad; Afia, Aziz El; Benkirane, Karim; Khafallah, Mohamed (Institute of Advanced Engineering and Science, 2024)
Conventional direct torque control (DTC) can be served to drive a dual three-phase permanent magnet synchronous motor (DTP-PMSM) by controlling the torque and speed. It relies on the direct application of controlled sequences through the use of a combination of dual hysteresis controllers with a transitioning table. In the course of conventional DTC implementation, there's generation of high armature current with lower-level harmonics, leading to increased losses that affect the machine's effectiveness. To enable a diminishment in these harmonics and consequently enhance the motor's efficiency, an approach to modify the conventional DTC is proposed. Specifically, this strategy involves adapting a new distribution of sectors and substituting the elements of the obtained switching table with synthetic elements. Simulated data validate the effectiveness of the chosen methodology.